Menafsir Ulang Persetujuan: Analisis Filosofis atas Syarat Substantif, Epistemis, dan Volisional Consent - Pratama, Mohammad Alvi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Consent is a fundamental normative concept in moral and social life, yet its complexity is often overlooked in everyday understanding. This article aims to philosophically examine the nature of consent as a normative power capable of transforming actions that were previously impermissible into permissible ones, while also analyzing the conditions that must be fulfilled for consent to be considered valid. This study employs a conceptual analysis method based on a literature review, examining major works in contemporary moral philosophy that discuss theories of consent. The analysis demonstrates that consent cannot be understood merely as an expression of individual will; rather, it functions as a normative mechanism that transforms the moral status of an action. However, its validity depends on the fulfillment of several crucial conditions: substantive conditions related to the nature of the action being consented to; epistemic conditions requiring adequate knowledge and understanding; volitional conditions ensuring freedom from coercion; and contextual conditions that take into account power relations and the surrounding social structures. Based on these findings, the article argues that consent constitutes a limited normative power, since its validity can only be recognized when these four conditions are fulfilled simultaneously.